2009
DOI: 10.1111/j.1365-2249.2009.04033.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen activated protein kinases: a role in inflammatory bowel disease?

Abstract: SummarySince their discovery more than 15 years ago, the mitogen activated protein kinases (MAPK) have been implicated in an ever-increasingly diverse array of pathways, including inflammatory signalling cascades. Inflammatory bowel diseases (IBD), such as ulcerative colitis and Crohn's disease, are characterized by the perpetual production of inflammatory mediators. Research into the transduction pathway behind this over-production has highlighted the potential mediating role for the MAPKs and their related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 78 publications
(127 reference statements)
1
114
0
1
Order By: Relevance
“…P38 MAPK pathway regulates inflammation through downstream proteins and kinases, affecting gene transcription directly and indirectly. 37 Activated p38 MAPK increases the recruitment and activation of lymphocytes and neutrophils and delays apoptosis of these cells, 9,38,39 which are the major source of perpetual production of inflammatory mediators. In the colon of mice with DSS-induced colitis, we found a high P38/Mk2 inhibition and WIN55 effect YY Li et al expression of both p38 MAPK and its phosphorylated form p-p38 in recruited inflammatory cells of the colonic submucosal plexus, together with the predicted effects: high expression and high levels of CINC-1/KC and MCP-1 and proinflammatory cytokines both in the local tissues and in the blood.…”
Section: Mk2 Deficiency and Win55 Administration Decrease Lung Mpo Acmentioning
confidence: 99%
“…P38 MAPK pathway regulates inflammation through downstream proteins and kinases, affecting gene transcription directly and indirectly. 37 Activated p38 MAPK increases the recruitment and activation of lymphocytes and neutrophils and delays apoptosis of these cells, 9,38,39 which are the major source of perpetual production of inflammatory mediators. In the colon of mice with DSS-induced colitis, we found a high P38/Mk2 inhibition and WIN55 effect YY Li et al expression of both p38 MAPK and its phosphorylated form p-p38 in recruited inflammatory cells of the colonic submucosal plexus, together with the predicted effects: high expression and high levels of CINC-1/KC and MCP-1 and proinflammatory cytokines both in the local tissues and in the blood.…”
Section: Mk2 Deficiency and Win55 Administration Decrease Lung Mpo Acmentioning
confidence: 99%
“…Moreover, MAPK including p38, JNK, and ERK1/2 are significantly activated in IBD (13)(14)(15)18). Thus we investigated whether J11-Cl can modulate the activity of MAPKs and NF-B.…”
Section: Modulation Of Pro-inflammatory Signalingmentioning
confidence: 99%
“…Several studies have reported enhanced expression and phosphorylation of MAPKs in the intestine of IBD patients, suggesting that MAPK inhibitors can be used as anti-inflammatory drugs in this disease (13)(14)(15). Activation of the NF-B pathway plays a crucial role in inflammation by inducing transcription of proinflammatory genes (16,17).…”
mentioning
confidence: 99%
“…This results in the translocation of NF-κB from the cytoplasm to the nucleus to promote the expression of various proinflammatory genes, including iNOS, COX-2, and cytokines (Lan et al 2012;Hayden and Ghosh 2014). The MAPKs, such as extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 MAPK, are signaling molecules that also play important roles in relaying inflammatory information from the extracellular space to the cytoplasm and nucleus to modulate inflammatory responses (Broom et al 2009;Patterson et al 2014). The activation of MAPKs by phosphorylation is a critical step in the production of proinflammatory molecules in activated macrophages.…”
Section: Introductionmentioning
confidence: 99%